2021
DOI: 10.3390/antiox10121923
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of Pipecolic Acid Biosynthetic Pathway in Drought Tolerance through the Antioxidant System in Tomato

Abstract: With global warming and water shortage, drought stress is provoking an increasing impact on plant growth, development, and crop productivity worldwide. Pipecolic acid (Pip) is an emerging lysine catabolite in plants, acting as a critical element in disease resistance with a related signal pathway of phytohormone salicylic acid (SA). While SA plays a vital role in various abiotic stresses, the role of Pip in plant response to abiotic stresses, especially drought, remains largely unknown. To address this issue, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The resulting supernatant was then used to measure enzymatic activity with a UV-2410PC spectrophotometer (Shimadzu, Japan). The activities of SOD, POD, CAT, and ascorbate peroxidase were measured according to the previously described protocol [ 47 ]. MDAR [ 48 ] and GST [ 49 ] enzymatic activities were measured following previous protocols.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting supernatant was then used to measure enzymatic activity with a UV-2410PC spectrophotometer (Shimadzu, Japan). The activities of SOD, POD, CAT, and ascorbate peroxidase were measured according to the previously described protocol [ 47 ]. MDAR [ 48 ] and GST [ 49 ] enzymatic activities were measured following previous protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Pipecolic acid is a lysine−derived non−protein amino acid which regulates plant systemic acquired resistance and basal immunity to bacterial pathogen infection [ 39 ]. Recent study has shown that pipecolic acid plays a negative regulatory role in drought tolerance of tomato plants [ 40 ]. In this study, the level of DL−pipecolic acid in DT decreased under mild drought stress, which may be related to the drought resistance response in DT.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants in plants have been classified into two main types: enzymatic and nonenzymatic antioxidants. The significant antioxidant enzymes in plant cells contain SOD, CAT, POD, and so on [ 63 ]. GSH and AsA are vital nonenzymatic antioxidants in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, APX, DHAR, and GR serve as significant enzymes in the AsA-GSH cycle [ 64 ]. Antioxidants are involved in multiple plant abiotic stresses, including heat stress [ 63 ]. Treating seedlings of Broussonetia papyrifera at high temperature, the activities of SOD, POD, and CAT were significantly increased [ 65 ].…”
Section: Discussionmentioning
confidence: 99%